Pengaruh Investasi, Jumlah Penduduk Miskin, dan Tingkat Pengangguran Terhadap Produk Domestik Regional Bruto (PDB) Tahun 2023 - Ajie Nugraha Pratama; Annasfitria Putri Hadi; Kamalia Uswatun Chasanah; M. Rafly Alfazari; Salma Eka Putri Syatibi (WACANA EKONOMI (Jurnal Ekonomi, Bisnis dan Akuntansi), 2025)
Economic growth is one of the main indicators of the success of a region's development. This study aims to analyze the influence of Foreign Direct Investment (FDI), the Number of Realized FDI Projects, the Number of Poor People, and the Unemployment Rate on Gross Regional Domestic Product (GRDP) in 34 Indonesian provinces in 2023. The method used is multiple linear regression analysis with a natural logarithm (log-log) model to facilitate the interpretation of elasticity between variables. The data used are secondary data with a cross-sectional approach. The results show that FDI and the Number of Realized FDI Projects have a positive and significant effect on GRDP. Similarly, the Number of Poor People and the Unemployment Rate have a positive and significant relationship with GRDP, which may reflect certain characteristics of provinces with high GRDP. The regression model has high explanatory power with an R-squared value of 83.55%, while the classical assumption test ensures that the model meets the BLUE (Best Linear Unbiased Estimator) criteria. This study concludes that foreign investment plays an important role in economic growth, while the relationship between poverty, unemployment, and GRDP requires further study to understand the causal mechanisms.